-7(a-6)=2-2a

Simple and best practice solution for -7(a-6)=2-2a equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -7(a-6)=2-2a equation:


Simplifying
-7(a + -6) = 2 + -2a

Reorder the terms:
-7(-6 + a) = 2 + -2a
(-6 * -7 + a * -7) = 2 + -2a
(42 + -7a) = 2 + -2a

Solving
42 + -7a = 2 + -2a

Solving for variable 'a'.

Move all terms containing a to the left, all other terms to the right.

Add '2a' to each side of the equation.
42 + -7a + 2a = 2 + -2a + 2a

Combine like terms: -7a + 2a = -5a
42 + -5a = 2 + -2a + 2a

Combine like terms: -2a + 2a = 0
42 + -5a = 2 + 0
42 + -5a = 2

Add '-42' to each side of the equation.
42 + -42 + -5a = 2 + -42

Combine like terms: 42 + -42 = 0
0 + -5a = 2 + -42
-5a = 2 + -42

Combine like terms: 2 + -42 = -40
-5a = -40

Divide each side by '-5'.
a = 8

Simplifying
a = 8

See similar equations:

| 4(x-3)=2x+2(x-6) | | 2x^6-17x^4+17x^3= | | 15x+45=180 | | ba-4b=c | | .5x+3=2 | | 6x^3-9x^2-216x+9=0 | | 25=-8+2(s-4) | | 3(a+b)=f | | 35x^2-9x-2=0 | | (-6x+7)=(19x-1) | | 9y+4-7y=124 | | -10(x-1)=-10x | | 0=4x^2+39x-10 | | -5b+6(1-b)=83 | | 2x^4-x^3-9x^2+13x-4=0 | | y-5=7(x-6) | | 2x^4-x^3-9x^2+13-4=0 | | b-a=d | | p^3-3p+2=0 | | 18y+3y=6 | | s(4+p)=m | | X+3.2=7.5 | | 5(+4)=18-9 | | 3(4-6k)+1=-131 | | 3y+18y=6 | | 36x^2-48x+16=1 | | -5q-2(1-q)=-6q | | -2-1=-x-3 | | 3x+3x+15+2x+5=180 | | 6m+3=3m+3 | | 45b+2=-15b+3 | | h+9.1=5.3 |

Equations solver categories